Positive kidney profile of dogs with Leishmania sp. and treated with miltefosine - Torres, Danillo Brenno de Assis; Pinheiro, Nelson Costa; Barros, Ellis de Sousa; Santos, Dennis Leite dos; da Silva, José Ribamar [UNESP]; Guerra, Porfírio Candanedo [UNESP] (Universidade Estadual de Londrina, 2024)
Canine leishmaniasis has a wide variety of clinical signs, and, depending on the stage of the disease, the kidneys are the organs most affected. To stage the disease and carry out treatment, kidney assessment is of great importance, along with drug interactions and the deposition of immune complexes. In this study, we evaluated the renal morphology and function by means of B-mode ultrasonography and vascular Doppler, biochemical, urinalysis, and blood pressure tests, correlating the findings in dogs positive for leishmaniasis and treated with miltefosine. For this, 38 dogs were used, 12 healthy (G1) ones and 26 naturally infected with Leishmania sp.; of these, 12 animals were not treated (G2), and 14 were treated with miltefosine (G3). Evaluations were performed twice, with an interval of 30 days, before and after treatment with miltefosine. The average values of blood pressure as well as biochemical and urinary parameters were within the normal ranges for the species. In the volumetric Doppler measurement, no statistical differences were observed for systolic velocity, diastolic velocity, and resistivity index between the kidneys and the treated and untreated groups. According to the results obtained, treatment with miltefosine does not influence the renal parameters evaluated.
Perfil renal de cães positivos para Leishmania sp. e tratados com Miltefosina
Keywords: Doppler; Kidneys; Leishmaniasis; Miltefosine